Kewenangan Badan Pengusahaan Batam Dalam Eksekusi Lahan di Kota Batam - Hanafi Hanafi; Emy Hajar Abra; Parningotan Malau (JURNAL USM LAW REVIEW, 2025)
The purpose of this study is to analyse the extent of juridical authority of Batam Management Agency in the process of land execution, and to review the extent to which such authority is exercised in accordance with the principles of law and justice. The authority possessed by BP Batam often causes polemics in the community, especially when there is a land vacancy or execution that is allegedly not accompanied by adequate juridical and social approaches. This research is important because it aims to understand the actual extent of BP Batam's authority in managing an area that falls within its jurisdiction. This research uses a normative research method, which examines the authority of BP Batam and the issues arising from such authority, especially in the community of Batam Island and its surroundings. Although BP Batam has the authority based on laws and regulations, the implementation of land executions often leads to social conflicts, such as those in Rempang and Galang Islands. There is a need for regulatory reform, separation of authority between the Mayor of Batam and the Head of BP Batam to avoid overlapping authority, and strengthening inter-institutional coordination through the establishment of local regulations or policies that favour the interests of the community. Tujuan penelitian ini adalah untuk menganalisis sejauh mana kewenangan Badan Pengelola Batam secara yuridis dalam proses eksekusi lahan, serta meninjau sejauh mana kewenangan tersebut dilaksanakan sesuai dengan prinsip-prinsip hukum dan keadilan. Kewenangan yang dimiliki BP Batam kerap menimbulkan polemik di tengah masyarakat, terutama ketika terjadi pengosongan atau eksekusi lahan yang diduga tidak disertai pendekatan yuridis dan sosial yang memadai. Penelitian ini sangat penting karena untuk memahami sampai mana sebenarnya kewenangan yang dimiliki oleh BP Batam dalam mengelola suatu wilayah yang termasuk otoritasnya. Penelitian ini menggunakan metode penelitian normatif yaitu meneliti mengenai kewenangan BP Batam dan hal-hal yang ditimbulkan dari kewenangan tersebut terutama di masyarakat pulau batam dan sekitarnya. Meskipun BP Batam memiliki otoritas berdasarkan peraturan perundang-undangan, pelaksanaan eksekusi lahan kerap kali menimbulkan konflik sosial, seperti yang terjadi di Pulau Rempang dan Galang. Perlu adanya pembaruan regulasi, pemisahan otoritas antara Wali Kota Batam dan Kepala BP Batam untuk menghindari tumpang tindih kewenangan, serta penguatan koordinasi antar lembaga melalui pembentukan perda atau kebijakan yang berpihak pada kepentingan masyarakat.